The lost lullaby and other stories about being an Armenian in Turkey - Bilal, Melissa. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2004., 2004)
This thesis tries to understand the experience of being an Armenian in Turkey today. It focuses on lullabies as a gendered medium of transmitting memories. By analyzing the change in the contexts within which lullabies are transmitted today, it argues that displacement and loss are two interrelated experiences shaping the sense of being an Armenian in Turkey. By conceptualizing these experiences as tools for understanding the cultural politics in Turkey, liberal perspective of multiculturalism is criticized in this thesis. It is argued that such a perspective dwells on the idea of dead cultures since it cuts the link between the past and the present with regard to the existence of different cultures in Anatolia and its destruction.In a context where the Armenian culture is represented as detached from its lived experiences and memory, it becomes impossible to share the grandmothers' stories in the public sphere and the loss itself becomes the experience of Armenianness. Young Armenians in Istanbul today, in their search for the Armenian identity, develop a certain way of belonging to the space and culture that is shaped very much by the experience of loss.
Keywords: Armenians -- Turkey.